PERISTIWA KOMUNIKASI, NILAI, DAN MAKNA SIMBOLIK RITUAL PETIK LAUT PADA KOMUNITAS NELAYAN DI DESA PADELEGAN KABUPATEN PAMEKASAN - Thariqatul Laily (ppjbsip, 2022)
Abstract: Padelegan Village is one of the villages located in Pademawu sub-district, North Sumatra regency Pamekasan. One example of ritual communication is Petik Laut. Petik Laut is a ritual that occurs in fishing communities.Petik Laut is a tradition that involves communication during the program. Petik Laut is a culture of local wisdom and is carried out from generation to generation. Petik Laut is held as a form of gratitude to those in power for the sustenance that has been given. Communication events (communicative event), the basis of which aims to explain the words in detail, describe in other words the analysis of events is a basic communication activity. The communication event has 8 components called SPEAKING. The research method used in this research is descriptive qualitative with ethnographic research design. The method was chosen based on the fact that the relationship between the categories and the data in this study will only be highlighted and explained in detail by the method.